Comparison of numerical and experimental results of structronic plate and shell structures - Köppe, Heinz; Gabbert, Ulrich; Laugwitz, Friedmann; Weber, Christian-Toralf (Computer Assisted Methods in Engineering and Science, 2023)
In the paper a general purpose finite element software for the simulation of piezoelectric materials and structronic (structure and electronic) systems is presented. The equations of coupled electromechanical problems are given in a weak form, which are the basis of the development of 1D, 2D, 3D as well as multi-layered composite shell elements. The smart structures finite element code includes static and dynamic analysis, where also controlled problems can be simulated. Two test examples are presented to compare the numerical results with measurements.